INTEGRATION OF THE CONTENT OF PROFESSIONAL MATHEMATICAL DISCIPLINES IN THE PROFESSIONAL TRAINING OF FUTURE MATHEMATICS TEACHERS - Shyshenko , Inna; Lukashova , Tetіana (Physical and Mathematical Education, 2022)
Formulation of the problem. Among the ways to integrate the content of professional mathematics disciplines in the training of future mathematics teachers should be singled out the fundamentalization of courses linear algebra and analytical geometry, mathematical analysis and analytical geometry, differential geometry through the development of integrated integrated special courses for future teachers.Materials and methods. System analysis of scientific, educational and methodical literature; comparison and synthesis of theoretical positions; generalization of own pedagogical experience and experience of colleagues from other institutions of higher education, some general mathematical and special methods of difference calculus.Results. The article considers the possibilities of studying professional mathematical disciplines in terms of integration of their content in the institution of higher pedagogical education of mathematical profile. The presentation of educational material in different training courses is mostly out of sync, as they are taught by different teachers. Instead, the future teacher of mathematics must be helped to form in his own mind a certain system of content of professional disciplines. Accordingly, we have developed special seminars for students of the Faculty of Physics and Mathematics, in which each teacher tries to provide interdisciplinary links of his course with others. The content was harmonized by defining related and identical concepts and their definitions, the sequence of introduction of primary and dependent terms, mutual references in professional mathematics to connections in the educational material, and so on.Conclusions. The formation of a knowledge base and other components of the learning system, taking into account interdisciplinary links, harmonization of learning content, and synchronization of the learning process over time can be implemented in various ways, including through the introduction of special seminars for students of physics and mathematics faculties. Integrating the content of education at the practical level gives students the most important opportunity from a pedagogical point of view: to independently form a personal knowledge system, add new information and form new connections in the system of professional competencies.
Keywords: training of future teachers of mathematics; professional mathematical disciplines; professional training; integration; content of education